Thermo-mechanical and micro-structural properties of xylanase containing whole wheat bread - G. Ghoshal; U.S. Shivhare; U.C. Banerjee (Food Science and Human Wellness)
Xylanase is a hemicellulase that can hydrolyses the complex polysaccharides. Hemicelluloses are main components of cell walls of cereal grains. Moreover, hemicelluloses are considered as potential sources of mono- and oligosaccharides. In this study, influence of xylanase on the physicochemical properties and sensory qualities of the whole wheat bread during storage was investigated. Studies of whole wheat bread on microstructure, texture, thermotics, Scanning Electron Microscopic (SEM), X-Ray Diffraction (XRD) were conducted at ambient temperature of 25 and 4 °C respectively. During storage at different temperatures, bread containing xylanase exhibited less firmness but larger volume with whiter crumb color and longer shelf life as compared to control bread. Results of firmness, enthalpy, Fourier Transformation Infra Red (FTIR) and X-Ray Diffraction (XRD) studies suggested a lower staling rate of bread containing xylanase as compared to control one. Bread containing xylanase showed a smoother surface and more uniform pore size than the control. Significant differences in microstructure of control and bread containing xylanase were observed which might be attributed due to the change in water starch gluten interaction. These differences were also found to be interrelated to the textural properties of bread. Better sensory features were achieved in bread containing xylanase.